2016
DOI: 10.17159/2222-3436/2016/v19n2a6
|View full text |Cite
|
Sign up to set email alerts
|

Can South Africa sustain and diversify its exports?

Abstract: The aim of this paper is to examine the diversification of South Africa's exports over the period 1994 to 2012. A decomposition of export growth shows that exports of non-fuel primary commodities as well as medium-skill and technology-intensive manufactured products increased. The largest decrease was in the export of resource-intensive manufactures. These changes reflect South Africa's endowment of relatively low levels of physical and human capital. The analysis shows that export products that are further fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Brenton, Saborowski et al (2010) suggest that firm entry rates into markets may be the same across different types of economies, but exit rates differ significantly. The results here are in line with export diversification from the extensive margin point of view (Matthee et al 2016), which is an increase in the number of trading partners (it can also be accompanied by an increase in the number of products exported) (Brenton and Newfarmer 2007;IMF 2014). South Africa needs to tap into the extensive sustainability margin to help with the structural transformation of the economy and the realization of export-led growth (Besedes and Prusa 2006), which is inclusive (Purfield et al 2014).…”
Section: Firm Survival In the Export Marketsupporting
confidence: 79%
See 1 more Smart Citation
“…Brenton, Saborowski et al (2010) suggest that firm entry rates into markets may be the same across different types of economies, but exit rates differ significantly. The results here are in line with export diversification from the extensive margin point of view (Matthee et al 2016), which is an increase in the number of trading partners (it can also be accompanied by an increase in the number of products exported) (Brenton and Newfarmer 2007;IMF 2014). South Africa needs to tap into the extensive sustainability margin to help with the structural transformation of the economy and the realization of export-led growth (Besedes and Prusa 2006), which is inclusive (Purfield et al 2014).…”
Section: Firm Survival In the Export Marketsupporting
confidence: 79%
“…This can be interpreted through the intensive export diversification argument. More productive exports are considered to reflect manufactured goods rather than raw natural resources (Matthee et al 2016). Market experience and expansion increase the chances of a firm's survival, and this is also supported by the literature (Inui et al 2017).…”
Section: Discrete Hazard Modelmentioning
confidence: 91%
“…Secondly, while the composition of South Africa's exports is changing, there is insufficient diversification into new and higher value products. Indeed, Matthee, Idsardi and Krugell (2016) reveal that since 1994, the highest export growth has been in non-fuel primary commodities (38%), while medium-skill, technology-intensive manufactures have grown by 22%. Resource-intensive manufactures have shown a serious decline in exports (around 50%).…”
Section: Introductionmentioning
confidence: 99%
“…The authors have, therefore concluded that the manner in which export diversification is obtained might play a significant role in explaining its influence on per capita income. In contrast with Naudé et al 2011, Matthee et al (2016) have shown for South Africa that exporting goods that are distant from the country's comparative advantage does not result in higher economic growth.…”
Section: Export Product Diversification and Services Export Diversifimentioning
confidence: 78%